Pemberdayaan Kader Posyandu Dalam Upaya Pencegahan Stunting Di Desa Tembelang, Candimulyo, Magelang - Rohmayanti; Afif Faisol Ludin; Muhammad Raditya Prayuga Utama; Risa Aminuha; Alvan Bagus Pradana (Jurnal Pengabdian Pada Masyarakat, 2022)
EMPOWERMENT OF POSYANDU CADRES IN STUNTING PREVENTION EFFORT IN TEMBELANG VILLAGE, CANDIMULYO, MAGELANG. Stunting is caused by a lack of nutritional intake received by the fetus or baby in the womb and in the early days of the child's birth. The lack of nutritional intake received by the baby is also caused by the lack of mother's knowledge about nutritional health before and during pregnancy and after the mother gives birth. Therefore, it is necessary to empower cadres so that they can provide education to mothers regarding stunting and its prevention. This activity aims to increase the knowledge and skills of cadres about early detection of stunting. The implementation of this activity is carried out in Tembelang Village, Candimulyo District, Magelang Regency in January-February 2022. There are stages carried out, namely the preparation stage including coordination, activity planning; implementation stage, namely socialization, formation of stunting cadres, counseling and training on stunting early detection, lactation management and complementary feeding; evaluation stage on knowledge and skills with post test. The result is an increase in cadre knowledge from an average value of 6.43 to 7.45. The increase in cadre skills from the average pre-test score was 8.35, while the post-test score increased to 8.92. The increase in the ability of cadres can be seen through observations when assisting cadres in early detection of stunting. It is recommended that cadres apply the knowledge gained from the training results. Early detection of stunting will be carried out by increasing the ability of cadres.